MiRAGDB: A Knowledgebase of RAG Regulators - Desai, Sagar Sanjiv; Whadgar, Saurabh; Raghavan, Sathees C.; Choudhary, Bibha (Frontiers in Immunology, 2022)
ABSTRACT RAG1 and RAG2 genes generate diversity in immunoglobulin and TCR genes by initiating the process of V-D-J recombination in immunoglobulin and TCR genes. RAGs recognize specific sequences (heptamer-nonamer) to generate a diversity of immunoglobulins. RAG expression is limited to early B and T cell developmental stages. Aberrant expression of RAG can lead to double-strand breaks and translocations as observed in leukemia and lymphoma. The expression of RAG is tightly regulated at the transcriptional and posttranscriptional levels. MicroRNAs (miRNAs) are small non-coding RNAs that are involved in the post-transcriptional regulation of gene expression. This study aimed to identify and catalog RAG regulation by miRNA during normal development and cancer. NGS data from normal B-cell and T-cell developmental stages, various cancer cell lines and blood cancer samples have been analyzed for the expression of miRNAs against RAG1 (1,173 against human RAG1 and 749 against mouse RAG1). The analyzed data has been organized to retrieve the miRNA and mRNA expression of various RAG regulators (10 transcription factors and interacting partners) in normal and diseased states. The database allows users to navigate through the human and mouse RAG regulators, visualize and plot expression. miRAGDB is freely available and can be accessed at http://52.4.112.252/shiny/miragdb/